Can binaural beats facilitate autonomic recovery following exposure to an acute stressor?. (November 2021) - Hautus, Michael J.; Shepherd, Daniel; Giang, Edmund; Landon, Jason
Abstract: Background and purpose: Binaural beats are seen as a new type of 'digital-drug'. The aim of this study was to determine if binaural beats could facilitate physiological recovery from a mental stressor. Materials and methods: 92 adults were exposed five times each to a 2-min mental stressor and a subsequent 4-min rest period containing silence or 1-of-4 examples of binaural beats (2, 5, 10, and 24 Hz). Physiological recovery across the five rest periods, as measured using skin conductance, heart rate, and breathing, were compared using one-way analysis of variance. Results: Binaural beats were linked to enhanced physiological recovery relative to silence. However, the expected pattern of results whereby lower frequency binaural beats would be associated with greater physiological recovery, was not observed. Conclusion: Our findings do not support a relationship between binaural beats and systematic changes in emotional states as measured physiologically. On the basis of our results the acute administration of binaural beats in primary care to lower sympathetic arousal cannot yet be considered an evidence-based practice.